The Charge of Thought-Policing in Universities - Poyraz, Suzan (Canadian Journal of Higher Education, 2006)
A phrase used for internal criticism within leftist movements in the 70s and 80s, “politically correct,” has now become equivalent to thought policing in the minds of many professional academicians. Taking University of Toronto as an example, this essay questions whether the thought policing (as enforcement of political correctness) accusation is justified, and if so, in what forms such enforcement could take place, and whether any of those are defensible. Three possible forms of enforcement are identified as curricular occupation, language control, and conflict of rights; among these, the last is the most severe. In terms of rights, the issue of political correctness is usually framed as a conflict between expression rights and equality rights. In a university, restriction of expression rights is not justified. However, expression rights need not be characterized as conflicting with equality rights if both those charged with policing and those who charge them genuinely respect each others’ expression rights.